Estimation of spatial distribution and health risk by arsenic and heavy metals in shallow groundwater around Dongting Lake plain using GIS mapping. (April 2021) - Long, Xiting; Liu, Fei; Zhou, Xin; Pi, Jing; Yin, Wei; Li, Fang; Huang, Shuping; Ma, Fang
Abstract: Potable groundwater has become the primary water source for the local population because of the serious pollution of As and heavy metals in the surface water around the Dongting Lake Plain. A comprehensive research on the shallow groundwater was performed in this study via geographical information system (GIS) and geochemical method to evaluate groundwater quality and health risks of shallow groundwater in Dongting Lake Plain. Eighty-seven samples were collected and the content of As and twelve other heavy metals (e.g., Al, Fe, Zn, Cu, Mo, Ni, Mn, Co, Ba, Pb, Cd, and Cr) in the samples were detected by inductively coupled plasma–mass spectrum (ICP-MS) technology. The water pollution situation was assessed using heavy metal contents and evaluation indices, and human health risks were evaluated on the basis of both carcinogenic and noncarcinogenic aspects. Results showed that the shallow groundwater quality is moderately to heavily contaminated and should be considered in some areas of the Li and Xiangjiang River coasts. Several regions have the potential of carcinogenic risks induced by As and the groundwater in some regions may have the risk of Cr carcinogenesis in the wet season. These findings suggested that the potential harm caused by Fe, Zn, Mn, Cr, and As pollution of groundwater, especially As and Cr in wet season, must be considered. The spatio-temporal study on the groundwater quality evaluation may be beneficial to the protection and sustainable development of groundwater resources in Dongting Lake Plain.Summary : Although the overall noncarcinogenic health risk by metals in shallow groundwater of Dongting Lake is low, noncarcinogenic health risks caused by Fe, Zn, Mn, and As exist in some areas. Highlights: Spatially interpolated distribution maps for groundwater As, heavy metals in shallow groundwater in Dongting Lake Plain. HPI and HEI assessments for two areas were moderate and severe in both wet and dry seasons. Noncarcinogenic health risks exist due to the presence of Fe, Zn, Mn, and As in some areas. Some regions may have potential carcinogenic risks induced by As and Cr.